Teacher capacity building strategy in writing scientific works - Abdillah, Maylane Boni (JPGI (Jurnal Penelitian Guru Indonesia), 2024)
This research is a qualitative research, in the form of an analysis of the causes of high school teacher difficulties in writing scientific papers as one of the development of teacher professionalism. Scientific writing or what is commonly called KTI is a written report on a scientific activity.The characteristics of an KTI can be studied from at least 4 aspects, namely presentation structure, components and substance, author's attitude, and written language. Efforts to improve teacher professionalism sometimes only focus on the learning process. Admittedly or not through scientific writing activities can improve teacher professionalism. In fact, teachers who currently occupy positions and ranks in existing groups feel that they still lack the ability to write scientific articles. Several observations and interviews with teachers when providing training related to scientific publications provide clarity on why teachers are not able, willing, and used to writing scientifically. One example of improving the teaching profession is through writing scientific papers. The teacher's efforts to improve his professionalism through writing scientific papers have not been maximized. In general, the development of teacher professionalism at SMA Negeri 1 Wanasari, Brebes Regency is through writing scientific papers, especially writing Classroom Action Research <w:LsdException Locked="false" Priority="47" Name="Grid Table 2